Korelasi Antara Kadar Ureum dan Kreatinin dengan Kadar Troponin I Pada Penderita Penyakit Jantung Koroner - Indriyani, Rosa (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Coronary Heart Disease (CHD) is a disease that begins with the emergence of atherosclerotic lesions that will involve cardiac enzymes. This study used troponin I enzymes because these enzymes produce high sensitivity and specificity and are released only when the heart is injured. The emergence of atherosclerotic lesions can also cause constriction of the renal blood vessels so that it can trigger an increase in urea and creatinine levels. The purpose of this study was to determine the correlation between urea and creatinine levels with troponin I levels in patients with coronary heart disease at Budhi Asih Hospital. The research method used was cross-sectional analytic observational with secondary data and 107 samples were used. This study used the Spearman correlation test with an alpha value of 0.05. The results showed that there was a correlation between troponin I and urea levels with a value of p = 0.003 (p <0.05) with a moderate level of relationship (r = 0.284). Likewise, the levels of troponin I and creatinine obtained a value of p = 0.001 (p <0.05) with a moderate level of relationship (r = 0.323). From the results of this study it can be concluded that there is a relationship between troponin I levels and urea and creatinine with a positive correlation direction indicating that if troponin I levels increase, urea and creatinine levels also increase